Awareness creation and impact assessment of meat retailers during Covid-19 lockdown in Mymensingh district - Din, MA; Rahman, KMM; Hashem, MA (Meat Research, 2023)
The COVID-19 pandemic impacted on meat production and its supply chain, and also meat prices. The research was conducted to evaluate the impact assessment of meat retailers during Covid-19 lockdown in Mymensingh District of Bangladesh. A total number of 50 meat retailers were surveyed from Mymensingh district for collecting necessary data and information. The experiment was conducted to increase awareness among meat retailers from February-April, 2021. An amalgam of descriptive statistics, mathematical and statistical analyses was used to analyze the data. It was observed that all the meat retailers faced problems in terms of selling meat and lowering return during the period of pandemic lockdown. During Covid-19 situation the income of meat retailers became lower compared to other conditions. Statistics showed that the income of meat retailers decreased about 60% during lockdown period. Results showed that average age, education and family size of meat retailers were 38 years, 5.84, and 5.98, respectively. The price of beef before, during and after lockdown was BDT 546, 512 and 550, respectively. The price of chevon before, during and after lockdown was BDT 804.16, 675 and 800.00, respectively. Similarly, the price of broiler meat and sonali chicken meat before, during and after lockdown was BDT 114.34, 106.52, 128.47; 189.47, 198.42, and 233.15, respectively. During Covid-19 situation the income of meat retailers became much lower as compared to any other critical conditions. About 90% meat retailers faced various problems towards buying and selling of animal, lack of consumers and lack of demand for meat. The prices of all kinds of meat such as beef, goat meat, and chicken meat became lessened during pandemic. During pandemic about 92% meat retailers used face mask for keeping them safe from corona virus. Only 10% people tested for corona virus. During lock down period it was seen that about 60% maintained physical distance at the time of selling of meat. During the time of pandemic lockdown 98% meat retailers did not get any financial support from government organizations or NGOs or any other private organizations. They did not also get any kind of help to create awareness from public health Department or from local authority. Despite facing all these problems, about 100% meat retailers liked to continue their meat business.